HUBUNGAN PERILAKU DIET DENGAN STATUS BERAT BADAN PADA WANITA PASCA MENIKAH - Edy Mulyono (ITKES Wiyata Husada Samarinda, 2019)
Background: In adulthood definitely want to have a healthy body, because with a healthy body will support life, but if the body is in an unhealthy state doing everything will be constrained. In addition to a healthy body, individuals also want to have an ideal body shape. Generally women assume that the ideal body is identical to a thin and slim body. Objective: To determine the relationship between dietary behavior and nutritional status in post-married women. Method: The research design in this study was a descriptive analytic design used to find the relationship between dietary behavior and nutritional status in post-married women. This type of research is quantitative with aapproach cross sectional, which was conducted in December 2018 with a sample of 88 people selected using thetechnique Convinience Sampling. Variable measurements were carried out using a questionnaire, hunting for height and weight. Results: No relationship between diet behavior with nutritional status in post-married women with ρ-value = 0.321. Conclusion: Diet behavior in this study suggests that unhealthy diet behavior is more dominant because dietary behavior can be influenced by intention and social support factors. The weight status in this study is more dominant with excess nutritional status (fat) because the incoming energy intake is more than the energy released.